2016
DOI: 10.2135/cropsci2016.05.0320
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and Soil Surfactants Affect Abamectin Distribution in Soil

Abstract: Nematodes are microscopic, soil‐dwelling organisms that adversely affect many turfgrass systems, including golf course putting greens. Abamectin controls many nematode species in golf course putting greens; however, high sorption to accumulated organic matter near the soil surface in established turfgrass systems may limit its distribution in soil, thereby limiting its efficacy. Field research was conducted on ‘A1/A4’ creeping bentgrass and ‘Champion’ ultradwarf bermudagrass putting greens to evaluate abamecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…Gannon et al. (2017) found similar results to our study. They determined that the soil surfactant Qualibra increased vertical distribution of abamectin in a soil column.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gannon et al. (2017) found similar results to our study. They determined that the soil surfactant Qualibra increased vertical distribution of abamectin in a soil column.…”
Section: Discussionsupporting
confidence: 93%
“…Latin and Ou (2018) determined that the soil surfactant Revolution, alone, had no effect on downward movement of propiconazole, azoxystrobin, pyraclostrobin, thiophanate‐methyl, or cabendazim in a field setting. In contrast, Gannon, Jeffries, and Ahmed (2017) found that the addition of the soil surfactant Qualibra (Syngenta) increased abamectin distribution in soil. Many soil surfactants reduce the surface tension between solution and soil particles, which is likely why abamectin distribution in the soil increased in this study.…”
Section: Introductionmentioning
confidence: 94%
“…Although the mobility of abamectin is low it is more toxic to M. incognita than fluopyram (Faske and Starr, 2006;Faske and Hurd, 2015), therefore, only a small amount was needed to cause a similar incidence of M. incognita mortality. The limited downward movement of abamectin in this study is comparable to other soil column and field studies (Gruber et al, 1990;Gannon et al, 2017). Though the downward movement of fluopyram was limited to 10 cm soil depth, the concentration detected would inhibit J2 infection of tomato (Faske and Hurd, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Abamectin had intermediate effects on nematodes, altering the community structure of free-living nematodes and causing disturbance to the soil ecosystem as indicated by a shift to a slightly less mature soil Nematicide effects on non-target nematodes in bermudagrass food web. Effects on nematodes were generally detected later in the season and could be explained by the characteristic slow movement of this formulation through the thatch layer of turfgrass (Gannon et al, 2017). High cp nematodes were mildly affected by abamectin.…”
Section: Discussion Abamectinmentioning
confidence: 96%